Top Five Causes of Neck Mass in Chattogram (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Identifying top problems in any discipline is very important for diagnosis and effective management. Unfortunately there is a knowledge gap in Chattogram, Bangladesh. To fill up the gap we have conducted the study.Materials and methods : It was a retrospective study based on hospital records of Chattogram General Hospital from January 2017 to December 2017. All (104) cases with neck mass were included. Age, sex, clinical diagnosis, histo-pathological diagnosis and management were noted. Data were managed manually.Results: Total 104 cases were studied among the cases 65% were female and 35% were male. 91% cases were of 10-50 years age group. Highest cases 33% were found in 20-30 years age group. According to Histo-pathological report 25% cases were Tubercular lymphadenopathy, Nonspecific lymphadenopathy were 17% and Multi-nodular goiter were 15%. Results were contrasted with previous studies.Conclusion: Top 05 causes of neck mass in Chattogram have been unveiled. Tuberculosis is still number one problem. So, TB control program should be evaluated further to find out causes of high TB cases in this region.Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 18-20